Security factors based evaluation of verification algorithm for an IoT access system - Al-Ghaili A.M.; Kasim H.; Othman M.; Hassan Z. (Springer Verlag, 2023)
Soft computing; Internet of Things (IOT); QR tag; Security Architecture; Security factors; Security objectives; Smart access; Smart city applications; Verification algorithms; Internet of things